2009
DOI: 10.1590/s0103-50532009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up HCl extractions by employing ultrasound energy to evaluate trace elements bioavailability in sediments

Abstract: Uma análise de variância de três fatores foi usada para testar a significância do tipo de recipiente, tipo de material e número de replicatas na preparação de amostras de sedimento utilizando um banho ultra-sônico. A extração convencional com HCl 1,0 mol L -1 , por 0,5, 4 e 12 h, foi modificada, e o banho ultra-sônico foi aplicado para diminuir o tempo de preparo de amostras. Os metais traço foram medidos por ICP OES. Os melhores resultados foram obtidos com frascos de Teflon ® com base plana. Com exceção do N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…With the bubbles implosion, there is a greater diffusivity of the solvent into the matrix. In addition, the ultrasound energy induces acoustic cavitation, which promotes an increase in temperature and pressure, which, with fragmentation by the shock waves, can increase the mass transfer of the analyte to the solvent (Hatje et al, 2009). Therefore, the use of this technology can lead to a better extraction of the compounds present in the matrix.…”
Section: Monomeric Anthocyaninmentioning
confidence: 99%
“…With the bubbles implosion, there is a greater diffusivity of the solvent into the matrix. In addition, the ultrasound energy induces acoustic cavitation, which promotes an increase in temperature and pressure, which, with fragmentation by the shock waves, can increase the mass transfer of the analyte to the solvent (Hatje et al, 2009). Therefore, the use of this technology can lead to a better extraction of the compounds present in the matrix.…”
Section: Monomeric Anthocyaninmentioning
confidence: 99%
“…According to Morse [38], the extraction in HCl 1 mol L −1 comprises the reactive phase of the metals, that is, the potentially more bioavailable. Huerta-Diaz and Morse [23], Townsend et al [52], Hatje et al [20], Machado et al [31], Peña-Icart et al [42] and Monte et al [36] also mention that this extraction is widely used in the determination of the bioavailability of metals in sediments.…”
Section: Bioavailable Metalsmentioning
confidence: 99%
“…Cavalcante et al 131 compared extraction techniques and clean-up procedures for PAH's analysis in sediments of the Ceará State (Brazil) coast and they observed that the highest recoveries were obtained with soxhlet and ultrasonic techniques. Hatje et al 132 investigated trace elements extractions with hydrochloric acid using factorial design. The authors concluded that the ultrasound-assisted leaching could reduce the conventional extraction time from 12 h to 50 min or even less (for Pb, for example).…”
Section: Environmentalmentioning
confidence: 99%